2015
DOI: 10.1371/journal.pntd.0003429
|View full text |Cite
|
Sign up to set email alerts
|

Novel Recombinant Multiepitope Proteins for the Diagnosis of Asymptomatic Leishmania infantum-Infected Dogs

Abstract: BackgroundVisceral leishmaniasis is the most severe form of leishmaniasis. Worldwide, approximately 20% of zoonotic human visceral leishmaniasis is caused by Leishmania infantum, also known as Leishmania chagasi in Latin America. Current diagnostic methods are not accurate enough to identify Leishmania-infected animals and may compromise the effectiveness of disease control. Therefore, we aimed to produce and test two recombinant multiepitope proteins as a means to improve and increase accuracy in the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 40 publications
0
47
1
Order By: Relevance
“…An alternative serological method that could be used to deal with the limitations presented by the protein mixture is the development of chimeric proteins, containing the regions of the proteins that presented the best performance in serological evaluations. Some studies in this area have already been done and they showed a significant improvement in the sensitivity of the serological test [ 46 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative serological method that could be used to deal with the limitations presented by the protein mixture is the development of chimeric proteins, containing the regions of the proteins that presented the best performance in serological evaluations. Some studies in this area have already been done and they showed a significant improvement in the sensitivity of the serological test [ 46 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The urgent need for a diagnostic test which offers increased degrees of sensibility and specificity prompted us to develop a recombinant multiepitope protein bearing HCV-specific immunodominant epitopes. Several studies have reported the successful use of multiepitope protein for diagnosis of infectious diseases such as leishmaniasis [ 22 ], hepatitis B [ 23 ], hepatitis C [ 12 ], toxoplasmosis [ 24 ], tuberculosis [ 25 ], leprosy [ 26 ], leptospirosis [ 27 ], dengue [ 28 ], and Chagas disease [ 29 ]. A multiepitope protein (r-HCV-F-MEP) for hepatitis C diagnosis has been previously developed bearing 5 immunodominant regions comprising genotypes circulating worldwide and one Indian isolate [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these two antigens exhibited higher sensitivity (85%) and specificity (93%) compared with their individual sensitivity and specificity (KLO8, 68% and 92%, respectively; rK26, 77% and 91%, respectively). Also, chimeric multi-epitope proteins are being engineered to improve the detection of asymptomatic infected dogs [ 64 ]. Novel approaches like immunoproteomics identified an uncharacterized hypothetical protein with high specificity and sensitivity for CVL [ 65 ].…”
Section: The Utility Of Standard and Newer Rapid Diagnostic Tests In mentioning
confidence: 99%